The contribution of amphibian macrophage subsets to scarless regeneration of skin wounds - Garvey Griffith, Christina N.; Hauser, Kelsey A.; Abramson, Bradley; Chapkin, Elissa R.; Jones, Elizabeth J.; Duttargi, Anju N.; Grayfer, Leon (Frontiers in Immunology, 2025)
Xenopus laevis juvenile frogs regenerate wounded skin without scarring, yet the underlying mechanisms driving this process remain poorly defined. Macrophages are critical to wound repair across vertebrates, and our results indicate a transient influx of macrophages into regenerating frog wounds. The colony stimulating factor-1 (CSF1) and interleukin-34 (IL34) growth factors control macrophage development. Through RNA in situ hybridization studies, we found that csf1 gene expression peaked early during juvenile frog wound responses, whereas il34 expression increased later in the repair process. Our past studies indicate that X. laevis CSF1- and IL34-differentiated macrophages are functionally distinct. Presently, we treated frog wounds with recombinant (r)CSF1 and rIL34 to determine the roles of the corresponding macrophage subsets in wound repair. Using a combination of RNA in situ hybridization, RNA sequencing and histology, we demonstrated that wounds skewed towards greater proportions of rCSF1-macrophages exhibited greater infiltration of leukocytes, chiefly amongst them neutrophils. These wounds also possessed robust expression of inflammatory genes and transcripts associated with granulation and fibrosis. By contrast, rIL34-treated frog wounds exhibited greater fibroblast activation concurrent with greater type I/III collagen ratios and expression of genes typically seen at later phases of wound repair. Together, we propose that while CSF1-macrophages are likely more prominently involved in the inflammatory phase of X. laevis wound repair, IL34-macrophages predominate the later reparative phase of these responses.